2022
DOI: 10.1186/s12889-022-14032-9
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian spatial modelling of malaria burden in two contrasted eco-epidemiological facies in Benin (West Africa): call for localized interventions

Abstract: Background: Despite a global decrease in malaria burden worldwide, malaria remains a major public health concern, especially in Benin children, the most vulnerable group. A better understanding of malaria's spatial and agedependent characteristics can help provide durable disease control and elimination. This study aimed to analyze the spatial distribution of Plasmodium falciparum malaria infection and disease among children under five years of age in Benin, West Africa. Methods:A cross-sectional epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…On the other hand, West Mamprusi had the highest RR in 2017 (RR: 4.43) and 2019 (RR: 3.08), but the lowest RR in 2020 (RR: 0.96). These findings support previous studies that examined spatial and temporal variations and found substantial spatial and temporal differences in malaria morbidity [ 5 , 7 , 9 – 12 ]. The finding that some districts are at the highest risk of malaria morbidity indicate serious threats to the progress in malaria control in Ghana, and interventions are urgently required to address this.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, West Mamprusi had the highest RR in 2017 (RR: 4.43) and 2019 (RR: 3.08), but the lowest RR in 2020 (RR: 0.96). These findings support previous studies that examined spatial and temporal variations and found substantial spatial and temporal differences in malaria morbidity [ 5 , 7 , 9 – 12 ]. The finding that some districts are at the highest risk of malaria morbidity indicate serious threats to the progress in malaria control in Ghana, and interventions are urgently required to address this.…”
Section: Discussionsupporting
confidence: 92%
“…The West Mamprusi, on the other hand, had the highest RR in 2017 (RR: 4.43) and 2019 (RR: 3.08), but the lowest RR in 2020 (RR: 0.96). These ndings support previous studies that examined spatial and temporal variations and found substantial spatial and temporal differences in malaria morbidity [5,7,[9][10][11][12]. The nding that some districts are at the highest risk of malaria morbidity signaled serious threats to the progress in malaria control in Ghana, and interventions are urgently required to address this.…”
Section: Discussionsupporting
confidence: 87%
“…Disease risk mapping is a powerful and robust technique for monitoring transmission and control efforts [4]. Likewise, malaria risk mapping is widely applied in spatial epidemiology using geostatistical methods such as Bayesian hierarchical spatial and spatiotemporal models [5][6][7][8]. Previous studies [9][10][11][12][13] in Ghana have applied Bayesian hierarchical spatial and spatiotemporal models to estimate the intensity of malaria transmission across regions of the country.…”
mentioning
confidence: 99%
“…In each commune two arrondissements were randomly selected: Tanguiéta (Tanguiéta, Taïacou) Matéri (Matéri centre, Tchanhoun-Cossi) Cobly (Cobly centre, Kountori). The climate is Sahelian and malaria prevalence during the dry season (November to April) is 50%, increasing to 78% during the rainy season (May to October) [ 26 ]. CHWs interface between health facilities and populations, delivering health promotion in the community.…”
Section: Methodsmentioning
confidence: 99%